A Role for Exocytosis in the Spatial Regulationof Actin Organization - Xiang-Dong Gao; Stefan Albert (The Scientific World Journal)
The efficient organization of the actin cytoskeleton is important for many cellular functions. However, how the local actin organization is regulated in a cell is not well understood. By using yeast mutants defective in actin organization and secretion, we demonstrated that exocytosis plays a role in the spatial regulation of actin organization. Our findings suggest that the actin cytoskeleton, exocytosis, and perhaps endocytosis, may depend on each other for efficiency and reinforce each other.